Effects of turbo-jav release conditions on distance of javelic throw - Maeda, M. (The Engineering of sport 7, Volume 1, 2008)
The turbo-jav is used in the javelic throw as an introduction to the javelin throw or as a technical tool with which to practice the javelin throw, The present study investigated the effects of turbo-jav release conditions on javelic throwing distance, Javelic throws of a turbo-jav by 14 university students were measured over 260 trials. Each turbo-jav throw was videotaped using two high-speed video cameras, and four standard-speed video cameras during flight. All conditions of turbo-jav release and flight were measured using the 3-dimensional (3D) DLT method. The results revealed a significant positive correlation between initial velocity and distance thrown using the javelic throw (r = 0.775, p < 0.01). The turbo-jav was thrown far even when the angle of attack was > 25°. The actual distance covered by a thrown turbo-jav was less than the theoretical throwing distance without air. In other words, the flight characteristics indicate that the flight of the turbo-jav in the javelic throw differs from that of a thrown javelin.